2015
DOI: 10.3758/s13423-014-0797-9
|View full text |Cite
|
Sign up to set email alerts
|

Learning, plasticity, and atypical generalization in children with autism

Abstract: Individuals with autism spectrum disorder (ASD) show accelerated learning in some tasks, degraded learning in others, and distinct deficits when generalizing to novel situations. Recent simulations with connectionist models suggest that deficits in cortical plasticity mechanisms can account for atypical patterns of generalization shown by some children with ASD. We tested the surprising theoretical prediction, from past simulations, that the children with ASD who show atypical generalization in perceptual cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 33 publications
7
41
0
Order By: Relevance
“…However, in a second analysis, we added a mixture component to isolate children that did not seem to rely on prototype processes. When focusing only on participants for which a prototype model seemed appropriate, the difference in sensitivity between HFASD and TD children largely disappeared, which is in line with recent evidence suggesting that HFASD children that extract a prototype are near-identical in sensitivity to TD children (Church et al, 2015). Yet, the Bayes factor testing for a difference primarily indicated that the present data are not sufficiently informative to decide either way.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, in a second analysis, we added a mixture component to isolate children that did not seem to rely on prototype processes. When focusing only on participants for which a prototype model seemed appropriate, the difference in sensitivity between HFASD and TD children largely disappeared, which is in line with recent evidence suggesting that HFASD children that extract a prototype are near-identical in sensitivity to TD children (Church et al, 2015). Yet, the Bayes factor testing for a difference primarily indicated that the present data are not sufficiently informative to decide either way.…”
Section: Discussionsupporting
confidence: 84%
“…The existence of different subgroups within the HFASD population should not come as a surprise (see, e.g., Caron et al, 2006;Church et al, 2015;Rajendran & Mitchell, 2007) and corroborates earlier evidence of multiple response patterns in these data . In our second analysis, about half of the HFASD children were assigned to a guessing group rather than the prototype group.…”
Section: Interpretation Of the Guessing Groupsupporting
confidence: 86%
“…Among new ideas, currently being explored is how different ways of presenting information (i.e. repeated examples of the ‘average’ of a category vs. multiple different examples of a category) can differentially support those with weaker or stronger patterns of generalisation [Church et al, ; Dovgopoly & Mercado 3rd., ]. Other strategies may include exploring different ways of structuring the learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…There are also other cognitive theories relevant to generalisation in autism [Brown & Bebko, ]. If generalisation is driven by the number of shared features across contexts, differences in generalisation could stem from how and where autistic individuals focus their attention, or what they consider salient in a particular context [Baron‐Cohen, ; Happe & Frith, ; Lovaas, Koegel, & Schreibman, ; Milton, ; Mottron, Dawson, Soulieres, Hubert, & Burack, ; Murray, Lesser, & Lawson, ; Plaisted, ], and/or how learned information is processed, organised and retrieved in memory [Baez & Ibanez, ; Church et al, ; McClelland, ; Miller, Odegard, & Allen, ; Schneider, Slaughter, Bayliss, & Dux, ; Williams, Goldstein, & Minshew, ]. These different perceptual and/or cognitive processes may mean that the features considered shared across two contexts by non‐autistic individuals may not consistently align with what autistic individuals perceive to be common elements.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying cause has been postulated as a deficit in cortical plasticity mechanisms [18]. Additionally, poor communication skills limit the child from receiving adequate social feedback necessary for learning [71].…”
Section: Shared Biochemical Mechanismsmentioning
confidence: 99%